Surface microstructures on planar substrates and textile fibers guide neurite outgrowth: a scaffold solution to push limits of critical nerve defect regeneration? - Stefan Weigel (Public Library of Science (PLoS), 2012)
The treatment of critical size peripheral nerve defects represents one of the most serious problems in neurosurgery. If the gap size exceeds a certain limit, healing can't be achieved. Connection mismatching may further reduce the clinical success. The present study investigates how far specific surface structures support neurite outgrowth and by that may represent one possibility to push distance limits that can be bridged. For this purpose, growth cone displacement of fluorescent embryonic chicken spinal cord neurons was monitored using time-lapse video. In a first series of experiments, parallel patterns of polyimide ridges of different geometry were created on planar silicon oxide surfaces. These channel-like structures were evaluated with and without amorphous hydrogenated carbon (a-C:H) coating. In a next step, structured and unstructured textile fibers were investigated. All planar surface materials (polyimide, silicon oxide and a-C:H) proved to be biocompatible, i.e. had no adverse effect on nerve cultures and supported neurite outgrowth. Mean growth cone migration velocity measured on 5 minute base was marginally affected by surface structuring. However, surface structure variability, i.e. ridge height, width and inter-ridge spacing, significantly enhanced the resulting net velocity by guiding the growth cone movement. Ridge height and inter-ridge distance affected the frequency of neurites crossing over ridges. Of the evaluated dimensions ridge height, width, and inter-ridge distance of respectively 3, 10, and 10 µm maximally supported net axon growth. Comparable artificial grooves, fabricated onto the surface of PET fibers by using an excimer laser, showed similar positive effects. Our data may help to further optimize surface characteristics of artificial nerve conduits and bioelectronic interfaces.